IN VITRO MULTIPLICATION OF IMPORTANT HORTICULTURE PLANTCITRUS RETICULATA (BLANCO.) - VISHWANATH WAGHMARE; NARAYAN PANDHURE (International Journal of Pharma and Bio Sciences, 2015)
Present research work was initiated role of BAP (benzyl amino purine),IAA and 2, 4-Don growth of callus and formation of multiple shoots by using shoot tip, leaf, and nodal explant. In vitro shoot tips, leaf and nodal segment explants were inoculated on MS media supplemented with different concentrations of BAP and IAA (Indole-3- acetic acid) to produce multiple shoots as well as Calli. Shoot tip explants inoculated on MS medium supplemented of2.6 mg/LBAP combination with 0.4 mg/LIAA produce the highest number of shoots per explant was observed. The average numbers of shoot per explants were observed 2.5 mg/L and 0.2 mg/L IBA and IAA respectively. However, nodal segments of C. reticulate inoculated on MS media containing 2 mg/LBAP and 1.5 mg/L IAA responsible for induction of callus was also observed.